Penentuan Harga Pokok Produksi Berdasarkan Metode Pesanan pada Mahasiswa - Valentina Monoarfa; Niluh Gede Julianti; Nurul Aliyah Abdulah; Marsyah Agustina Wagiu; Revalina (Economic Reviews Journal, 2025)
Determining the cost of production is an important aspect of cost management in various industries, including the education sector. This study aims to analyze the order-based costing method for students, focusing on its impact on operational efficiency and decision-making. The order method allows institutions to calculate production costs accurately based on the specific needs of each project or study program. Data were collected through surveys and interviews with students and lecturers at several universities. The results of the analysis show that the use of this method not only increases cost transparency but also encourages students to better understand the production process and cost management. This study recommends the widespread application of the order method in educational environments to improve accountability and efficiency in resource management.